HUBUNGAN ANTARA DINAMIKA KELOMPOK DENGAN TANGGAP ADOPSI INOVASI BUDIDAYA SALAK PONDOH THE RELATIONSHIP BETWEEN GROUP DYNAMICS AND RESPONSE TO INNOVATION ADOPTION OF SNAKE FRUIT PONDOH CULTIVATION - , Djoni; Maulana, Feri Arif (Pembangunan Pedesaan, 2009)
The objectives were to find out group dynamics and the farmers response and to analyze their relationship on innovation adoption of snake fruit Pondoh cultivation, partially and simultaneously. A case study was used in the research. Kelompok Tani Mekar Jaya II in Ciakar Village, Cibeureum District and Kelompok Tani Sinarjaya in Urug Village, Kawalu District, Tasikmalaya City was purposively chosen. All members (40 farmers of each group) were chosen as respondents. The primary data on the dynamics and the response were analyzed descriptively and the relationship was analyzed using non-parametric statistics test. The hypothesis test was simultaneously done by the W Kendallâs test and partially by the Rank Spearmanâs correlation test. The research results showed that the dynamics and the response was categorized high; simultaneously there was relationship between the dynamics and the adoption or the more dynamic the group the higher the adoption would be. Partially, it was shown that: a) there was relationship between the groups objective, task structure, solidness, and the response to the adoption b) there was no relationship between the group assistance, pressure, effectiveness, and the response to the adoption; c) there was no relationship between the group structure and the response to the adoption of either in the Mekar Jaya II or the Sinarjaya; d) there was relationship between the group atmosphere and the response to the adoption of the Mekar Jaya II farmerâs, on the contrary, there was no relationship between the structure and the response to the adoption of the Sinarjaya.